Working memory genetics in schizophrenia and related disorders: an RDoC perspective - Schwarz, Emanuel; Tost, Heike; Meyer-Lindenberg, Andreas (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2016)
Improved classification of mental disorders through neurobiological measures will require a set of traits that map to transdiagnostic subgroups of patients and align with heritable, core psychopathological processes at the center of the disorders of interest. A promising candidate is working memory (WM) function, for which deficits have been reported across multiple diagnostic entities including schizophrenia, bipolar disorder, ADHD, autism, and major depressive disorder. Here we review genetic working memory associations and their brain functional correlates from the perspective of identifying patient subgroups across conventional diagnostic boundaries, explore the utility of multimodal investigations integrating functional information at the neural systems level and explore potential limitations as well as future directions for research.
Gesehen am 18.01.2019
Article first published online in Wiley Online Library (wileyonlinelibrary.com): 14 September 2015